Судження як логічна форма мислення - Новіков, Ю. Ю. (ХНУРЕ, 2023)
This work is devoted to the study of the concept of judgment, as well as the form of logical thinking. The concept of judgment, the forms of representation of judgments, terms and their relationship in judgment, the material realization of judgments are considered. The main types of judgments are considered in more detail and their examples are presented.